Pengaruh Penambahan Serbuk Kaca Dan Abu Sekam Pada Tanah Lunak Berdasarkan Uji Konsolidasi - Dyah Pratiwi Kusumastuti; Irma Sepriyanna Sepriyanna (FORUM MEKANIKA, 2019)
It can not be avoided when the construction must stand on soft soil, then the construction will suffer damage due to subsidence or congestion from soft soil. To improve soft soils as one part of the construction of them is the method of chemical stabilization of the soil. The stabilizer material mixed was 10% glass powder and the percentage of husk ash was 0%, 2.5%, 5%, 7.5% and 10% of the dry weight of the original soil sample. Changes in the characteristics of soft soil and stabilized soils are reviewed based on the consolidation test. Based on the results of the study, the value of the void ratio decreases with increasing glass dust and husk ash, where the lowest void ratio is 0.5328 obtained in the addition of 10% glass powder and 7.5% husk ash. A decrease in the void ratio indicates a decrease in the compression index (Cc) and the swelling index (Cs). The lowering of the compression index and the swelling index indicate that the addition of glass powder and husk ash causes the soft soil sample to become denser. The lowest compressive index and swelling index values ​​were obtained in soil sample specimens with the addition of 10% glass powder and 10% husk ash, which respectively decreased by 35.165% and 75.757% when compared to the condition of the original soil sample.